Interactions of Word Formation and Vocabulary on the Material of Nests of Single-Rooted Words in Russian - Khadzhikurbanova Gulbahor Aslitdinovna (Zien Journals, 2023)
This article shows the importance of studying the problems of the interaction of word formation and vocabulary on the material of nests of single-rooted words, as well as, identified and described all system-forming units, defined the functions and role of different units of word formation in the ordering of lexical relations of words, considered the lexical and word-forming nests.
Keywords: vocabulary; word formation; nests; single-rooted words